1997
DOI: 10.1161/01.cir.96.7.2144
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia Pneumoniae , Cytomegalovirus, and Herpes Simplex Virus in Atherosclerosis of the Carotid Artery

Abstract: C. pneumoniae and CMV are commonly detected in atherosclerotic plaques of the carotid arteries, but their presence cannot be predicted by measuring serum antibodies. The presence of these microorganisms may predispose to a greater risk of thrombosis in the plaques, but further studies are needed to confirm this observation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
171
5
19

Year Published

2000
2000
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(200 citation statements)
references
References 25 publications
5
171
5
19
Order By: Relevance
“…29,30 In addition, TLR9 expressed by pDCs may recognize endogenous danger signals in the atherosclerotic plaque. In particular, self-DNA is able to trigger pDCs via TLR9.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 In addition, TLR9 expressed by pDCs may recognize endogenous danger signals in the atherosclerotic plaque. In particular, self-DNA is able to trigger pDCs via TLR9.…”
Section: Discussionmentioning
confidence: 99%
“…34 Also, it can still be argued that viral infections, not affected by macrolide treatment, are involved in atherogenesis, arterial thrombosis and plaque rupture. 35,36 Recently, Ad infections were considered to play a role in the development of obesity and are associated with plasma lipid abnormalities. 15,17,18,37,38 In the present study it is shown that a range of different viral and bacterial microorganisms are able to infect human adipocytes and induce an inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological data (9)(10)(11)28) indicate the frequent infection of arteries with microbial pathogens. It is conceivable that successful immune responses against these pathogens are crucial to limit direct cytopathic and indirect immunopathological damage during vascular infections.…”
Section: Mutual Chronic Perpetuation Of Vascular Inflammation and Chomentioning
confidence: 99%
“…In humans, herpesvirus DNA or antigen can be found in atherosclerotic lesions in patients with coronary artery disease (9,10). In addition, there is a correlation between seroreactivity against Chlamydia pneumoniae and coronary heart disease (11), and C. pneunoniae antigen can be detected in patients with carotid artery stenosis (10).…”
mentioning
confidence: 99%